Enhancing Dopamine Detection Using a Glassy Carbon Electrode Modified with Aluminum Oxide, Titanium Dioxide, and Poly(3,4-ethylenedioxythiophene)-(4-styrenesulfonate) - Siti Fauziyah Rahman; Gilar Wisnu Hardi; Elly Septia Yulianti; Siti Hanafiah; Muhammad Artha Jabatsudewa Maras; Yudan Whulanza; Don Hee Park (International Journal of Technology)
Dopamine is an important neurotransmitter involved in signal transmission to the brain. Deficiencies in dopamine are associated with various neurological disorders, such as schizophrenia, attention deficit hyperactivity disorder, and Parkinson's disease. In this study, a novel non-enzymatic electrochemical sensor for dopamine detection was developed using aluminum oxide/titanium dioxide/poly(3,4-ethylenedioxythiophene)-poly(4-styrenesulfonate) (Al2O3/TiO2/PEDOT:PSS) composite modified glassy carbon electrode (GCE). Al2O3/TiO2/PEDOT:PSS composite exhibited enhanced catalytic activity for the oxidation of dopamine due to the increase of the working electrode’s surface area. Using the cyclic voltammetry (CV) method, dopamine was detected in the range of 50–1000 M in 0.1 M phosphate-buffered saline (PBS) solution at pH 7.0, with a determined limit of detection of 6 M. Since this nanocomposite modification showed low cost, easy process, and high performance, Al2O3/TiO2/PEDOT:PSS modified GCE may be a good candidate for the development of a non-enzymatic dopamine sensor.